2015
DOI: 10.1111/ffe.12324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shot peening parameters on high‐cycle fatigue strength of steel produced by powder metallurgy process

Abstract: In this study, the effect of shot peening parameters on fatigue strength of steel manufactured by powder metallurgy (PM) was investigated. Steel material obtained from Höganas ASC 100.29 in chemical composition of Fe–0.5% C–2% Cu was produced by using a single action press PM process. To determine the effect of shot peening parameters on fatigue performance, fatigue tests were performed on 20 unpeened and 80 shot‐peened samples, which were machined from sintered steel. Furthermore, shot‐peened samples were pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, an interesting issue related to this type of material is that it can be efficiently used for the manufacturing of complexly shaped components by means of the modern production techniques of additive manufacturing (AM). In particular, the aptitude of processing metallic materials and of fabricating geometrically complicated three‐dimensional parts or even microstructures makes this technique a really promising technology . The main applications are currently in the fields of microelectro‐mechanical systems (MEMS) in that of biomechanics and in blade manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an interesting issue related to this type of material is that it can be efficiently used for the manufacturing of complexly shaped components by means of the modern production techniques of additive manufacturing (AM). In particular, the aptitude of processing metallic materials and of fabricating geometrically complicated three‐dimensional parts or even microstructures makes this technique a really promising technology . The main applications are currently in the fields of microelectro‐mechanical systems (MEMS) in that of biomechanics and in blade manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the aptitude of processing metallic materials and of fabricating geometrically complicated three-dimensional parts or even microstructures makes this technique a really promising technology. 7,8 The main applications are currently in the fields of microelectro-mechanical systems (MEMS) in that of biomechanics and in blade manufacturing. For instance, Clare et al 9 used the technology of selective laser melting to build three-dimensional Ni-Ti MEMS.…”
mentioning
confidence: 99%
“…Roland et al [7] and Yang et al [8] showed that a stainless steel with surface mechanical attrition treatment and a pure Cu with surface mechanical grinding treatment had higher fatigue strength than the original materials, especially in high cycle fatigue regime. Other articles [10][11][12][13][14][15] also reported similar results of different materials with various types of surface treatments. All these investigations attributed the enhancement of the fatigue strength for the treated specimens or components to the grain refinement and the compressive residual stress caused by surface strengthening treatment.…”
Section: Introductionmentioning
confidence: 68%
“…Several models exist for the competing mechanisms to predict fatigue behavior influenced by surface roughness and residual stresses . Additional process modeling efforts also predict the residual stress fields and surface roughness resulting from the shot peening process …”
Section: Introductionmentioning
confidence: 99%